Development of an evaluation scheme for senior residents in Otorhinolaryngology - Gloria-Cruz, Teresa Luisa I.
Evaluation is established as one of the essential components of an effective educational program. The Department of Otorhinolaryngology of the UP-PGH Medical Center maintains excellence and leadership through relevant training of future specialists. However, the evaluation of the residents in training is presently unstructured and unclear. This project thus aimed to develop an evaluation scheme for graduating residents as an initial step in producing an evaluation plan for all year levels of residents. The objectives are to determine the preferences of the key players in the residency training program regarding the purpose, focus sources of data, evaluators, methods, tools and frequency, and management of an evaluation scheme; to compare the variability of the preferences of the different groups of respondents; to infer from the perceptions of the key players the framework for evaluating senior residents; and to design an evaluation plan for senior residents. This is a research and development study design. The research part included a review of literature, use of previous knowledge and experience and a needs assessment or preferences survey regarding the various components of the evaluation scheme. Development of the evaluation plan included information collection and analysis using the results of the survey and field testing of formulated and adopted tools of assessment. The final product is an evaluation scheme or plan for senior residents of Otorhinolaryngology. Results of the survey were subjected to qualitative and quantitative analyses of data. Based on these, the purpose of evaluation was inferred to be both formative and summative. The domains or foci to be evaluated included not only Knowledge, Skills and Attitudes but also Research, Teaching, and Administrative outputs. The standard of evaluation will be based on the department's existing learning objectives and the combination of percentage allocations that was preferred by the most number of respondents was Knowledge=40%, Surgical skills=30%, Attitudes=15% and Research Outputs=15%. Teaching and administrative achievements will only be assessed for formative purposes. The preferences survey indicated, in varying degrees, that the consultants, residents, OR staff, Ward staff, were considered as appropriate evaluators of residents' performance. There was an overwhelming preference for the chief resident as an evaluator and a majority response for excluding the self as an evaluator for summative purposes. Preferred data collection procedures for the evaluation were the written, oral and practical examinations, as well as rating scales for attitudes, surgical skills and overall clinical competence. The survey also revealed the overwhelming positive response to the willingness to participate in the evaluation scheme by the respondents and their belief in the worthiness of the proposal . These, among others, were considered in the management plan of the evaluation scheme. Although evaluation of residents in the Department of Otorhinolaryngology exists, there is a need for a more structured, more systematic and therefore more meaningful scheme. This project developed an evaluation scheme for senior residents in Otorhinolaryngology that may be useful, not only in its original setting, but in other training institutions.